(untitled) (Indian Journal of Public Health Research & Development, 2024)
Background: Primary health care being the first level of contact, constitutes the process of continuing health care and seeks support from the rest of the health system. This support would be required in the areas of (a) consultation on health problems, (b) referral of patients to local or other specialized institutions; (c) supportive supervision and guidance and (d) logistic support and supplies. Materials & Methods: A community based cross-sectional study was conducted among the adult decision maker female of the households in the rural field practice area of Department of Community Medicine, Government Medical College, Amritsar after approval from Institutional Ethics committee. The collected data were entered into MS Excel and analyzed using Epi info software version 7. Descriptive statistics were presented in frequency and percentages and Chi-square test applied to assess the statistical association. Results: Out of the total 1521 respondents, 995 women visited the nearest public health facility to avail services while 526 women did not avail any service. Amongst 1521 respondents, 1144, 642 and 1257 respondents had ever met MPHW(F), MPHW(M) and ASHA worker respectively; out of these, 87.9% respondents were satisfied with the behaviour of MPHW(F), 84.4% with MPHW(M) and 73.6% with the behaviour of ASHA worker. Conclusions: The proportion of respondents satisfied with the behaviour of attending doctor or health worker was seen to be more in village with Subsidary Health centre as Public health facility followed by village with Subcentre and village without any public health facility.